2013
DOI: 10.1152/ajpheart.00578.2013
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional effects on cardiac tissue induced by moderate zinc deficiency during prenatal and postnatal life in male and female rats

Abstract: The aim of this study was to evaluate whether moderate zinc restriction in rats throughout fetal life, lactation, and/or postweaning growth results in early changes in cardiac morphology predisposing the onset of cardiac dysfunction in adult life as well as sex-related differences in the adaptation to this nutritional injury. Female Wistar rats received low or control zinc diets from the beginning of pregnancy up to offspring weaning. After being weaned, offspring were fed either a low or control zinc diet unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These alterations were related to changes in apoptosis, inflammatory cytokines, growth factors expression, oxidative stress and NO system. On the other hand, females would be less sensitive to this micronutrient deficiency since they exhibited no significant structural or functional cardiac alterations and lower changes in NO system [22,23,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations were related to changes in apoptosis, inflammatory cytokines, growth factors expression, oxidative stress and NO system. On the other hand, females would be less sensitive to this micronutrient deficiency since they exhibited no significant structural or functional cardiac alterations and lower changes in NO system [22,23,56].…”
Section: Discussionmentioning
confidence: 99%
“…In both 6-and 81-day-old rats, Picrosirius Red staining allowed us to measure perivascular collagen area (CA), expressed as the CA/LA ratio ((μm 2 /μm 2 )*100) in 5-μmthick aortic sections [23]. Collagen fibers in aortic tunica media of 81-day-old rats were evaluated on a subjective scale ranging from 0 to 4 (0: very poor staining of collagen fibers, 1: poor, 2: moderate, 3: intense, 4: very intense).…”
Section: Histological Analysis Of Thoracic Aortamentioning
confidence: 99%
“…However, the cardiomyocytes continue to proliferate for a while in the postnatal period. 2 Several elements are important to maintain the integrity of this system, such as zinc, which is necessary for the cardiac development, 3 and tryptophan, which is important for the development of the cardiorespiratory center in the medulla oblongata. 4 Thus, a balanced diet is essential for pregnant women to promote a healthy development of the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, marginal zinc deficiency intake in adulthood can also induce zinc accumulation and oxidative stress in the mammary tissue [20]. Other experimental studies have showed that moderate-tosevere zinc deficiency during fetal life and lactation has shown adverse effects on rat blood pressure and renal and cardiac function in adult life [21][22][23].…”
Section: Introductionmentioning
confidence: 99%